2021
DOI: 10.21608/bjas.2021.199035
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Progesterone-primed ovarian stimulation in polycystic ovarian syndrome: RCT

Abstract: Background: In vitro fertilization for women with polycystic ovarian syndrome is an essential (PCOS). New methods to improve clinical outcomes are still needed. Objective: this research investigated the effectiveness of PPOS and compared it with the standard PCOS antagonist regimen. Materials and procedures: A total of 76 PCOS women eligible for aided therapy of reproductive technology were recruited in this RCT from February 2020 to May 2021 and put in random two groups (n=38/per group). Since the sixth day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
2
0
0
Order By: Relevance
“…The comparable effectiveness of the two evaluated protocols in our study aligns with findings from previous studies, including the four prospective randomized controlled trials (23)(24)(25)(26), two prospective non-randomized controlled trials (27,28), nine retrospective studies covering various topics (29)(30)(31)(32)(33)(34)(35)(36)(37)(38), and four reviews (39)(40)(41)(42) . These studies have consistently reported similar outcomes when comparing the use of PPOS and GnRHan protocols, both overall and specifically among infertile women with polycystic ovary syndrome who underwent intracytoplasmic sperm injection-frozen embryo transfer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The comparable effectiveness of the two evaluated protocols in our study aligns with findings from previous studies, including the four prospective randomized controlled trials (23)(24)(25)(26), two prospective non-randomized controlled trials (27,28), nine retrospective studies covering various topics (29)(30)(31)(32)(33)(34)(35)(36)(37)(38), and four reviews (39)(40)(41)(42) . These studies have consistently reported similar outcomes when comparing the use of PPOS and GnRHan protocols, both overall and specifically among infertile women with polycystic ovary syndrome who underwent intracytoplasmic sperm injection-frozen embryo transfer.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, the self-funded nature of infertility treatment in our country should be taken into consideration. clinical outcomes obtained from both FPPOS protocol and the FGnRHan protocol on freeze-all cycles conducted on ladies with PCOS were shown to be similar, this aligns with the Turkan's retrospective analysis of 258 ladies in the progestins group and 267 ladies in the GnRHan group (38) and with Egyptian RCT involved 76 PCOS ladies (24). The FPPOS group exhibited a greater duration of stimulation and total dose of Gn compared to the FGnRHan group, which aligns with findings from prior studies (29-Our research suggests that the FPPOS protocol may be a viable alternative to the WHO-recommended GnRHan protocol for ladies with PCOS who are classified as hyper respondents in terms of COS (43)(44)(45)(46)(47).…”
Section: Discussionsupporting
confidence: 73%